Anti‐tumor activity of WK88‐1, a novel geldanamycin derivative, in gefitinib‐resistant non‐small cell lung cancers with Met amplification. Issue 10 (25th September 2014) - Jang, Won‐Jun; Jung, Sung‐Keun; Kang, Jong‐Soon; Jeong, Joo‐Won; Bae, Moon‐Kyoung; Joo, Sang Hoon; Park, Gyu Hwan; Kundu, Joydeb K.; Hong, Young‐Soo; Jeong, Chul‐Ho
<x xml:space="preserve">Abstract</x> Although epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKIs) have been introduced for the treatment of non‐small cell lung cancer (NSCLC), the emergence of secondary T790M mutation in EGFR or amplification of the Met proto‐oncogene restrain the clinical success of EGFR‐TKIs. Since heat shock protein‐90 (Hsp90) stabilizes various oncoproteins including EGFR and c‐Met, the inhibition of Hsp90 activity appears as a rational strategy to develop anticancer drugs. Despite preclinical efficacy of geldanamycin‐anasamycin (GA)‐derivatives containing benzoquinone moiety as Hsp90 inhibitors, the hepatotoxicity of these GA‐derivatives restricts their therapeutic benefit. We have prepared WK‐88 series of GA‐derivatives, which lack the benzoquinone moiety. In this study, we have examined the anticancer effects of WK88‐1 in Met‐amplified‐ and gefitinib‐resistant (HCC827GR) NSCLC cells and its parental HCC827 cells. Treatment with WK88‐1 reduced the cell viability in both HCC827 and HCC827GR cells, which was associated with marked decrease in the constitutive expression of Hsp90 client proteins, such as EGFR, ErbB2, ErbB3, Met and Akt. Moreover, WK88‐1 attenuated phosphorylation of these Hsp90 client proteins and reduced the anchorage‐independent growth of HCC827GR cells. Administration of WK88‐1 did not cause hepatotoxicity in animals and significantly reduced the growth of HCC827GR cells xenograft tumors in nude mice. Our study provides evidence that ErbB3 might be a client for Hsp90 in Met‐amplified NSCLCs. In conclusion, we demonstrate that inhibition of Hsp90 dampens the activation of EGFR‐ or c‐Met‐mediated survival of Met‐amplified NSCLCs and that WK88‐1 as a Hsp90 inhibitor alleviates gefitinib resistance in HCC827GR cells.